Thermoelectric Properties of ZnO Thin Films Grown by Metal-Organic Chemical Vapor Deposition. Issue 1805 (10th July 2015) - Kucukgok, Bahadir; Hussain, Babar; Zhou, Chuanle; Ferguson, Ian T.; Lu, Na
ABSTRACT: Thermoelectric (TE) materials have gained renewed interests in last decades for both power generation and energy conservation from waste-heat harvesting. Research in the discovery of best TE materials such as, bulk materials, complex structures, and low dimensional play crucial role to achieve high efficiency TE materials. Wide bandgap materials like ZnO can be promising candidate for high efficiency TE power generation owing to its low-cost, nontoxicity, and stability at high temperatures. In this paper, room temperature TE properties of thin film ZnO grown by metal organic vapor deposition (MOCVD) are reported. TE properties of thin film GaN are also studied as reference to that of thin film ZnO. Moreover, high resolution x-ray diffraction (HRXRD), room temperature photoluminescence (PL) with deep ultraviolet (DUV) spectroscopy (excitation at 248nm), hall effect, and thermal gradient methods have been employed to investigate the effect of structural, optical, electrical, and thermal properties of the samples, respectively. The effect of doping concentrations and structural defects on Seebeck coefficients of thin film ZnO are systematically studied and discussed in this work.